EU INTERESTS IN DEVELOPING ARCTIC SEA ROUTES - N. I. Vorobyev (Vestnik MGIMO-Universiteta)
The article considers the European Union’s key strategic interests in the increased use of the Arctic routes, especially the Northern Sea Route (NSR), but also the Northwest Passage. This issue is high on the agenda given the EU dependence on the maritime transport accounting for the predominant share of the Union’s trade. The EU technological, financial and human resources can contribute greatly to the development if the Arctic seaways which would in turn benefit the member states. The author notes that the EU has already actively engaged in designing the framework regulation for the Arctic maritime shipping including the legal, environmental and safety provisions. Securing an innocent passage of ships through the Arctic waters is one of the main objectives in this regard considering that none of the EU members are Arctic coastal states. Another issue at stake is delivering Arctic oil and gas reserves highly important for the EU to the continent for which developed seaborne transport is crucial. The article also gives an overview of the EU practical steps with regards to the Arctic routes including projects aimed at connecting the Union’s transport system with the Russian North West and potentially the NSR. It is noted that the EU is highly interested in exploiting the potential of the Arctic sea routes and focuses on international cooperation to achieve the goal. Increased EU cooperation with the Arctic coastal states including Russia would be mutually beneficial given the opportunities the new routes offer and the EU resources that can be used to support their development.